Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

The Laplace Transform Review: ECE 382 Fall 2012

Download as pdf or txt
Download as pdf or txt
You are on page 1of 15

ECE 382 Fall 2012

The Laplace Transform Review


by
Stanislaw H. Żak

1 Definition
The Laplace transform is an operator that transforms a function of time, f (t), into a new
function of complex variable, F (s), where s = σ+jω, as illustrated in Figure 1. The operator
L denotes that the time function f (t) has been transformed to its Laplace transform, denoted
F (s). The Laplace transform is very useful in solving linear differential equations and hence

f (t) F (s) = L(f (t))


- L -

Figure 1: Schematic representation of the Laplace transform operator.

in analyzing control systems.


To obtain the Laplace transform of the given function of time, f (t),
1. multiply f (t) by a converging factor e−st . This is a factor that decreases to zero as
time increases to infinity;

2. Integrate f (t)e−st with respect to time between the limits 0− and ∞ to obtain the
Laplace transform of f (t),
Z ∞
F (s) = L(f (t)) = f (t)e−st dt
0−

The lower limit of integration is 0− , rather than 0, to account for the effect of “instanta-
neous energy transfer”.

1
F (s) f (t) = L−1 (F (s))
−1
- L -

Figure 2: Schematic representation of the inverse Laplace transform operation.

The above definition of the Laplace transform is also referred to as the one-sided or
unilateral Laplace transform. In the two-sided, or bilateral, Laplace transform, the lower
limit is −∞. For our purposes the one-sided Laplace transform is sufficient.
If we want to reverse the operation and take the inverse transform, back to the time
domain, we write
L−1 (F (s)) = f (t).
Taking the inverse Laplace transform is illustrated in Figure 2.
Because we are using the one-sided Laplace transform, we define all functions, whose
Laplace transforms we compute, to be zero for t < 0− . To proceed, we recall the definition
of the unit step function, u(t),
(
1 if t ≥ 0
u(t) =
0 if t < 0.

The unit step function is also called the Heaviside function.

Example 1 Find the Laplace transform of

f (t) = e−at u(t),

where a is a real constant. A graph of f (t) for a = 3 is shown in Figure 3. We have


Z ∞ Z ∞
−at −at −st
L(e u(t)) = e e u(t)dt = e−(a+s)t dt.
0− 0−

The above integral exists if


<(a + s) > 0.

2
Figure 3: A plot of e−3t u(t).

The region of the s-plane for which the Laplace transform exists is called the Region of
Convergence and abbreviated ROC. Since s = σ + jω, the ROC, in our example, is the
region in the s-plane where

0 < <(a + s) = <(a + σ + jω) = a + σ,

that is, the region where σ > −a. Proceeding with the integration, we obtain

1 −(a+s)t 
 
−at
L(e u(t)) = − e 
a+s  −
0
1 −(a+s)∞ 1 −(a+s)0−
   
= − e − − e .
a+s a+s
For s in the ROC, the first term tends to zero. Hence,

1
L(e−at u(t)) =
s+a

3
Using the Laplace transform of the exponential function, we can easily find the Laplace
transform of the unit step. Indeed, if a = 0, then f (t) = e−at u(t) = u(t). Hence,

1
L(u(t)) = (1)
s

2 Linearity Property of the Laplace Transform


The Laplace transform of the sum, or difference, of two functions of time is equal to the
sum, or difference, of the transforms of each function, that is,

L (f1 (t) ± f2 (t)) = L (f1 (t)) ± L (f2 (t)) (2)

Indeed,
Z ∞
L (f1 (t) ± f2 (t)) = (f1 (t) ± f2 (t)) e−st dt

Z0∞ Z ∞
−st
= f1 (t)e dt ± f2 (t)e−st dt
0− 0−
= L (f1 (t)) ± L (f2 (t)) .

The Laplace transform of the product of a real or complex constant K and a time function
f (t) is equal to the product of the constant and the transform of the time function, that is,

L (Kf (t)) = KL (f (t)) . (3)

Indeed, Z ∞ Z ∞
L (Kf (t)) = Kf (t)e−st dt = K f (t)e−st dt = KL (f (t)) .
0− 0−
The above two properties can be represented in the form

L (Kf1 (t) ± f2 (t)) = KL (f1 (t)) ± L (f2 (t))

Example 2 To find the Laplace transform of

f (t) = Ku(t),

where K is a constant, we can use (3) and the Laplace transform of the unit step, given
by (1), to obtain
K
L (Ku(t)) = KL (u(t)) = .
s

4
Example 3 We will use the linear property of the Laplace transform to find the Laplace
transform of
f (t) = sin ωt.
First, recall the Euler formula,

ejωt = cos ωt + j sin ωt.

Hence,
e−jωt = cos ωt − j sin ωt.
Subtracting the second of the above expressions from the first one and dividing the result
by 2j gives
ejωt − e−jωt
sin ωt = .
2j
Therefore,
ejωt − e−jωt
! !
1  jωt −jωt

L (sin ωt) = L =L e −e .
2j 2j
Applying to the above (3) yields
1  jωt 
L (sin ωt) = L e − e−jωt .
2j
Applying now (2), we obtain
1   jωt   
L (sin ωt) = L e − L e−jωt .
2j
We then use twice the formula for the Laplace transform of the exponential to get
!
1 1 1
L (sin ωt) = − .
2j s − jω s + jω
Performing algebraic manipulations gives
ω
L (sin ωt) =
s2 + ω2

Similarly, we obtain
ejωt + e−jωt
!
L (cos ωt) = L .
2
Hence,
s
L (cos ωt) =
s2 + ω2

5
3 Laplace Transforms of Derivatives
We will now show that !
df (t)  
L = sF (s) − f 0−
dt
where F (s) = L(f (t)) and f (0− ) is the initial value of f , that is, the value of f at 0− . Thus,
differentiating in the time domain corresponds to multiplying F (s) by s and then subtracting
the initial value of f (t). To derive the above formula, we apply the definition of the Laplace
transform, ! Z ∞
df (t) df (t) −st
L = e dt, (4)
dt 0− dt
and then evaluate the integral by integrating by parts. Recall that the formula for integrating
by parts can easily be derived from the formula for the derivative of the product of two
functions. We use the notation,
du(t)
u0 = .
dt
Then, we have
(uv)0 = u0 v + uv 0 .
Integrating the above and rearranging gives
Z Z
0
u v = uv − uv 0 . (5)

We let
df
u0 = and v = e−st .
dt
Then applying (5) to (4), we obtain
! Z ∞
df (t) −st
∞  
L =e f (t)
 − − f (t) −se−st dt.
dt 0 0−

Assuming that f (t) is Laplace transformable, the value of e−st f (t) at t = ∞ is zero. Hence,
the right-hand side of the above reduces to
! Z ∞
df (t) 

  
L = −f 0 +s f (t)e−st dt = sF (s) − f 0− .
dt 0−

Thus, we showed that differentiation in the time domain corresponds to an algebraic opera-
tion in the s domain.
Using the Laplace transform of the first derivative of a time function, we can easily
determine the Laplace transform of higher-order derivatives. Indeed, to find the Laplace
2
transform of d dtf 2(t) , we let
df (t)
g(t) = .
dt

6
Then, !
df (t)  
L(g(t)) = G(s) = L = sF (s) − f 0− . (6)
dt
Note that
d2 f (t) dg(t)
2
= .
dt dt
Hence,
df 2 (t)
! !
dg(t)  
L =L = sG(s) − g 0− .
dt2 dt
Substituting into the above (6) gives
df 2 (t)
!
    
L = s sF (s) − f 0− − g 0− .
dt2
df (0− )
Observing that g (0− ) = dt
, we get

df 2 (t) df (0− )
!
 
L = s2 F (s) − sf 0− −
dt2 dt

Successively applying the above arguments, we can obtain the Laplace transform of the n-th
time derivative,

df n (t) df (0− ) dn−2 f (0− ) dn−1 f (0− )


!
 
L = sn F (s) − sn−1 f 0− − sn−2 − ··· − s −
dtn dt dtn−2 dtn−1

4 Solving Differential Equations Using Laplace Trans-


form
We now illustrate how to use the Laplace transform and inverse Laplace transform to solve
linear ordinary differential equations. After taking the Laplace transform of both sides of
a differential equation and performing required manipulations in the s domain, we need to
reconstruct the solution in the time domain. This is achieved using the inverse Laplace
transform.
Example 4 We will solve the following differential equation using the Laplace transform,
d2 x(t) dx(t)
2 2
+7 + 5x(t) = 10u(t),
dt dt
subject to the initial conditions
dx (0− )  
= 1, x 0− = −2,
dt

7
where u(t) is the unit step function.
We take the Laplace transform of both sides of the differential equation to get

d2 x(t)
! !
dx(t)
2L 2
+ 7L + 5L (x(t)) = 10L (u(t)) .
dt dt

Using Laplace transforms of time derivatives of a function of time and the Laplace transform
of the unit step function, we obtain

dx (0− )
!


    10
2
2 s X(s) − sx 0 − + 7 sX(s) − x 0− + 5X(s) = .
dt s

Substituting into the above the initial conditions and rearranging gives
  10 10 − 4s2 − 12s
2s2 + 7s + 5 X(s) = − 4s − 12 = .
s s
Hence,
−4s2 − 12s + 10 −2s2 − 6s + 5 −2s2 − 6s + 5
X(s) = = = . (7)
s (2s2 + 7s + 5) s (s2 + 3.5s + 2.5) s (s + 2.5) (s + 1)
We now need to reconstruct the solution of the differential equation in the time domain. In
other words, given X(s) we want to obtain x(t) in which x(t) is zero for t < 0 such that
X(s) = L(x(t)). Thus,
x(t) = L−1 (X(s)) .
To proceed, note that X(s) as given by (7) is a rational function of s, that is, X(s) is a ratio
of two polynomials in s, in which the degree of the numerator with respect to s is smaller
than the degree of the denominator. Such a rational function is called strictly proper and
can be expanded into a sum of partial fractions by writing a term or a series of terms for
each zero of the denominator. We obtain
K1 K2 K3
X(s) = + + . (8)
s s + 2.5 s + 1
We will now compute the constants Ki ’s. We can do so by representing the right-hand side
of the above as a rational function and then comparing the resulting numerator with the
numerator of (7). We represent (8) as

K1 (s + 2.5) (s + 1) + K2 s (s + 1) + K3 s (s + 2.5)
X(s) =
s (s + 2.5) (s + 1)
(K1 + K2 + K3 ) s2 + (3.5K1 + K2 + 2.5K3 ) s + 2.5K1
= (9)
s (s + 2.5) (s + 1)

8
Comparing coefficients of like powers of the numerators of (7) and (9) gives three algebraic
equations in three unknowns,

K1 + K2 + K3 = −2 


3.5K1 + K2 + 2.5K3 = −6 
5 = 2.5K1

Solving the above system of equations gives

K1 = 2, K2 = 2, K3 = −6.

Substituting the above into (8) yields


2 2 6
X(s) = + − .
s s + 2.5 s + 1
Applying the inverse Laplace transform to the above, we obtain
2 2 6
 
x(t) = L + −
s s + 2.5 s + 1
2 2 6
     
= L +L −L

s s + 2.5
s+1
−2.5t −t
= 2 + 2e − 6e u(t).

5 Laplace Transforms of Integrals


We first consider taking the Laplace transform of
Z t
f (x)dx. (10)
0−

Let F (s) denote the Laplace transform of f (t), that is, F (s) = L(f (t)). We find the Laplace
transform of (10) using integration by parts to obtain
Z t  Z ∞ Z t 
L f (x)dx = f (x)dx e−st dt. (11)
0− 0− 0−

Recall the formula for integration by parts,


Z Z
0
u v = uv − uv 0 .

Let Z t
1
u = − e−st and v = f (x)dx.
s 0−

9
Note that
dv d Zt
= f (x)dx = f (t).
dt dt 0−
Integrating (11) by parts gives
∞ 1 Z ∞ −st
Z t Z t
1
 
L f (x)dx = − e−st f (x)dx + e f (t)dt.
0− s 0−
 −
0 s 0−
The first term on the right-hand side is zero at both the lower and upper limits. The value
at the lower limit, t = 0− , is clearly zero. The value at the upper limit, t = ∞, is zero
because we assumed that f (t) is Laplace transformable. Hence,
Z t
F (s)

L f (x)dx = (12)
0− s
We next find the Laplace transform of
Z t
f (x)dx. (13)
−∞

Applying the definition and using the fact that the Laplace transform is linear yields
Z t  Z 0− ! Z t 
L f (x)dx = L f (x)dx + L f (x)dx = F1 (s) + F2 (s).
−∞ −∞ 0−

The limits of the first integral are constant, therefore the integral will be a constant. Hence,
R 0−
−∞ f (x)dx
F1 (s) = ,
s
while by (12),
F (s)
F2 (s) = .
s
Therefore,
R 0−
f (x)dx
Z t
F (s)

−∞
L f (x)dx = + (14)
−∞ s s
Example 5 We find the Laplace transform of the voltage, vC (t), across a capacitor C. We
have
1 Zt
vC (t) = i(x)dx.
C −∞
Using (14) gives
1 R 0−
1 I(s) C −∞
i(x)dx
L (vC (t)) = + .
C s s
R 0−
Since −∞ i(x)dx is the charge, q, on the capacitor at t = 0− and v = q/C, we obtain
1 I(s) vC (0− )
L (vC (t)) = +
C s s

10
6 More Properties of the Laplace Transform
We will now show that translation in the time domain corresponds to multiplication by an
exponential in the s domain, that is,

L (f (t − a)u(t − a)) = e−sa F (s), a>0

where F (s) = L(f (t)). We have


Z ∞ Z ∞
L (f (t − a)u(t − a)) = f (t − a)u(t − a)e−st dt = f (t − a)e−st dt, (15)
0− a−

because u(t − a) = 0 for t < a. Next, we change the variable of integration. We let

x = t − a.

Then, x = 0− when t = a− , x = ∞ when t = ∞, and dx = dt. Substituting the above


into (15) yields
Z ∞ Z ∞
−s(x+a) −sa
L (f (t − a)u(t − a)) = f (x)e dx = e f (x)e−sx dx = e−as F (s),
0− 0−

which is the desired result.

We will now prove the time/frequency scaling property,

1 s
 
L(f (at)) = F , a>0
a a

Indeed, applying the Laplace transform yields


Z ∞
L(f (at)) = f (at)e−st dt. (16)
0−

Let x = at. Then, dt = a1 dx. Substituting the above into (16) gives

1Z ∞ 1 s
 
s
L(f (at)) = f (x)e−( a )x dx = F ,
a 0− a a
which was to be shown.

11
Figure 4: Generating the unit impulse function as the limit of the pulse functions.

7 The Impulse Function and Its Properties


The impulse function, denoted δ(t), also called the Dirac function, is a signal of infinite
amplitude, zero duration, and unity area. We can construct an impulse function as the limit
of pulse functions
1
pεi (t) = (u(t) − u(t − εi ))
εi
as εi → 0. This is illustrated in Figure 4. Note that the pulse functions have the following
features as εi → 0:

1. the amplitude approaches infinity,

2. the duration of the pulses approaches zero,

3. the area under each pulse is constant; in our example the area equals unity.

The unit impulse function is defined as


Z ∞
δ(t)dt = 1 and δ(t) = 0 for t 6= 0.
−∞

The above definition states that the area under the impulse function is constant. The area
represents the strength of the impulse function. The impulse function of strength K is
denoted Kδ(t). Its graphical representation is depicted in Figure 5. The strength of the
impulse is shown next to the arrow’s head. The shifted impulse function of strength K is
also shown in Figure 5. The unit impulse function can be thought of as a derivative of the

12
Figure 5: A graphical representation of the impulse Kδ(t) and Kδ(t − a).

unit step function, that is,


du(t)
δ(t) = .
dt
The function shown in Figure 6 approaches the unit step function as ε → 0. The function
shown in Figure 7, which is the derivative of the function from Figure 6, approaches the unit
impulse function as ε → 0.
The impulse function has the sifting property,
Z ∞
f (t)δ(t − a)dt = f (a)
−∞

where f (t) is a continuous function of time. It follows from the above that the impulse
function sifts out everything except the value of f at t = a—hence the name of the property.
To verify the validity of the sifting property, we note that δ(t − a) is zero everywhere except
at t = a. Hence, we can write,
Z ∞ Z a+ε
f (t)δ(t − a)dt = f (t)δ(t − a)dt.
−∞ a−ε

By assumption, f is continuous at a. Therefore, it must take the value of f (a) as t → a.


Thus, Z a+ε Z a+ε
f (t)δ(t − a)dt = f (a) δ(t − a)dt = f (a),
a−ε a−ε

which was to be demonstrated.


Using the sifting property we can show that

L(δ(t)) = 1

13
Figure 6: The function u approaches the unit step as ε → 0.

Figure 7: The derivative of uε (t) shown in Figure 6. As ε → 0, δε (t) approches δ(t).

14
Indeed, applying the definition of the Laplace transform and using the sifting property, we
obtain Z ∞ Z 0+
−st 0
L(δ(t)) = δ(t)e dt = e δ(t)dt = 1.
0− 0−
We now discuss another important property of the impulse function—the sampling prop-
erty. Since δ(t − a) = 0 for t 6= a,

f (t)δ(t − a) = 0 for t 6= a

as is
f (a)δ(t − a) = 0 for t 6= a.
However, when t = a, we have

f (t)δ(t − a) = f (a)δ(t − a) for t = a

provided that f (a) exists. Therefore,

f (t)δ(t − a) = f (a)δ(t − a) for all t

The above property is called the sampling property of the impulse function.
Examples

(i) (cos 3t)δ(t − π) = (cos 3π)δ(t − π) = −δ(t − π);

(ii) e−2t δ(t) = e−2(0) δ(t) = δ(t);

(iii) (1 − e−4t ) δ(t) = (1 − e0 ) δ(t) = 0δ(t) = 0.

15

You might also like